Men's hopes, fears and challenges in engagement in perinatal health and the prevention of mother-to-child transmission of HIV in rural Kenya. Issue 11 (2nd November 2018) - Musoke, Pamela; Hatcher, Abigail; Rogers, Anna Joy; Achiro, Lillian; Bukusi, Elizabeth; Darbes, Lynae; Kwena, Zachary; Oyaro, Patrick; Weke, Elly; Turan, Janet M.
Abstract: Male involvement in antenatal care has been shown to improve health outcomes for women and infants. However, little is known about how best to encourage male partners to support essential perinatal health activities. We explored men's perceptions of facilitators and barriers to involvement in antenatal care and HIV prevention including fears, hopes and challenges. Forty in-depth interviews were conducted with the male partners of HIV-positive and HIV-negative pregnant women in southwest Kenya. Most male partners believed engaging in pregnancy health-related activities was beneficial for keeping families healthy. However, thematic analysis revealed several obstacles that hindered participation. Poor couple relationship dynamics seemed negatively to influence male engagement. Some men were apprehensive that clinic staff might force them to test for HIV and disclose the results; if HIV-positive, men feared being labelled as 'victimisers' in situations of serodiscordancy, and described fears of abandonment by their wives. Some men avoided accompanying their wives, citing local culture as rationale for avoiding the 'effeminate' act of antenatal care attendance. Amidst these obstacles, some men chose to use their partners' HIV status as proxy for their own. Findings suggest that improving male engagement in essential maternal and child health-related activities will require addressing both structural and interpersonal barriers.